The Role of Social Media as a Media for Disseminating Academic Information to Journalism Students at UIN Syarif Hidayatullah Jakarta - Sabrina; Wahyunengsih (CV. Multi Kreasi Media, 2023)
The development of Communication Technology is a special issue that cannot be resolved. This has implications for changes in human behavior when interacting. One group that is very vulnerable to the development of communication technology is the student group. The purpose of this study is to better understand the role of social media as a source of academic news for students of the Journalism Study Program at Syarif Hidayatullah Islamic State University, Jakarta. This research uses a qualitative methodology and data collection methods using in-depth interviews with eight students. According to this study, informants use 5 to 10 hours every day to access the internet, There are two specific apps that are used in this scenario: Instagram and WhatsApp. Currently, social media is the main source used by departments to find academic information compared to going directly to the dean's, rector's office, or other locations.